2001
DOI: 10.1038/sj.onc.1204588
|View full text |Cite
|
Sign up to set email alerts
|

Detection of differentially expressed genes in human colon carcinoma cells treated with a selective COX-2 inhibitor

Abstract: Numerous reports suggest that use of nonsteroidal anti-in¯ammatory drugs (NSAIDs) decrease mortality from colorectal cancer. To better understand all of the mechanisms underlying this e ect, the global pattern of gene expression in colon carcinoma cells following treatment with NS-398, a selective cyclooxygenase-2 inhibitor was evaluated. We utilized suppression subtractive hybridization combined with di erential screening to identify genes whose expression was a ected following treatment. Among the subtracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 59 publications
4
66
1
1
Order By: Relevance
“…It is also identified as a correlate of induced apoptosis (Shibahara et al, 1995;Zhang and DuBois, 2001) and cellular senescence (Kang et al, 2002). In the present work, we now suggest Pdcd4 to suppress the invasion cascade of cultured colon cancer with two different models.…”
Section: Pdcd4 Regulates Invasion and U-par Expression Jh Leupold Et Alsupporting
confidence: 56%
See 1 more Smart Citation
“…It is also identified as a correlate of induced apoptosis (Shibahara et al, 1995;Zhang and DuBois, 2001) and cellular senescence (Kang et al, 2002). In the present work, we now suggest Pdcd4 to suppress the invasion cascade of cultured colon cancer with two different models.…”
Section: Pdcd4 Regulates Invasion and U-par Expression Jh Leupold Et Alsupporting
confidence: 56%
“…The human gene is located at chromosome 10q24 (Soejima et al, 1999) and its expression has been reported, for example, in human interleukin 12 (IL-12)-induced natural killer (NK) and T cells (Azzoni et al, 1998), small duct epithelial cells of the normal mammary gland (Soejima et al, 1999;Yoshinaga et al, 1999), a growth-suppressed human neuroendocrine pancreatic carcinoma cells (Stalberg et al, 2001), normal human lung tissue (Chen et al, 2003), or senescent human fibroblasts (Kang et al, 2002). Pdcd4 has been suggested to be linked to the process of apoptosis in response to different inducers (Shibahara et al, 1995;Zhang and DuBois, 2001), and has been shown to be regulated by topoisomerase inhibitors (Onishi et al, 1998), COX-2 inhibitors (Zhang and DuBois, 2001), Myb (Schlichter et al, 2001) and Akt (Palamarchuk et al, 2005). Molecules regulated by Pdcd4 include p21 (Go¨ke et al, 2004), Cdk4, ornithine decarboxylase (Jansen et al, 2005), carbonic anhydrase II (LankatButtgereit et al, 2004) and JNK/c-Jun/AP-1 (Bitomsky et al, 2004;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, arsenite treatment suppressed transcription of some proteasome components, as was observed using cDNA microarray analysis [81]. In contrast, COX-2 inhibitors have been shown to suppress transcription of several matrix metalloproteinases and to upregulate Dynamin-2 gene expression, which controls protein export and endocytosis in the cell [72,82,83]. General inhibition of endocytosis in melanomas by phenylarsine oxide (PAO; 1 μM) [84], which appears to suppress recycling membrane FasL, also substantially increased surface expression of FasL (Fig.…”
Section: Effects Of Inhibition Of the Proteasome On Fasl Surface Exprmentioning
confidence: 94%
“…A distinct subset of genes is regulated by the COX-2 inhibitor (Zhang and DuBois, 2001), and alteration in gene expression programming could be a target in the anticancer activity of COX inhibitors. The diminishing of Egr-1 and c-fos by celecoxib may reduce their target gene activation involved in controlling cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that inhibitors of COX-2, but not COX-1, strongly suppress cell growth by inducing apoptosis (Erickson et al, 1999;Ding et al, 2000;Elder et al, 2000;Lui et al, 2000;Uefuji et al, 2000;Williams et al, 2000;Grosch et al, 2001), which may result from blocking the cell cycle, enhancing c-myc expression, and diminishing bcl-2 expression (Elder et al, 2000). In addition, among genes differentially expressed in cells treated with the specific inhibitor of COX-2, several other genes involved in the regulation of cell adhesion, cell cycle progression, apoptosis, and differentiation were found (Zhang and DuBois, 2001). While these results provided evidence that antineoplastic effects of nonsteroidal anti-inflammatory drugs (NSAIDs) may result from altered expression of genes that regulate various biological processes, the molecular mechanisms mediating antiproliferative effect of COX inhibitors are still not well defined.…”
mentioning
confidence: 99%